2016
DOI: 10.1194/jlr.m064592
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of long-chain acyl-CoA synthetase 1 variants with fasting glucose, diabetes, and subclinical atherosclerosis

Abstract: The enzyme long-chain acyl-CoA synthetase 1 (ACSL1), which catalyzes conversion of free long-chain fatty acids into their acyl-CoA derivatives, has emerged as a metabolic rheostat in mouse skeletal muscle, heart, and adipose tissue ( 1-3 ). Thus, mice defi cient in ACSL1 in skeletal muscle exhibit a marked reduction in fatty acid utilization through ␤ -oxidation and a concomitant increase in glucose utilization during fasting, and they are hypoglycemic during endurance training ( 4 ). In the heart, which relie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…LPS activates inflammatory responses in monocytes/macrophages via ACSL1 [ 17 ]. Our data showed that the inhibition of ACSL1 significantly blocked the LPS-induced production of GM-CSF, which is supported by the study that ACSL1-deficient mouse macrophages display reduced inflammatory responses after long-term stimulation with LPS [ 18 ].…”
Section: Discussionsupporting
confidence: 83%
“…LPS activates inflammatory responses in monocytes/macrophages via ACSL1 [ 17 ]. Our data showed that the inhibition of ACSL1 significantly blocked the LPS-induced production of GM-CSF, which is supported by the study that ACSL1-deficient mouse macrophages display reduced inflammatory responses after long-term stimulation with LPS [ 18 ].…”
Section: Discussionsupporting
confidence: 83%
“…53 Additionally, ACSL1 (Gene ID: 2180), also known as acyl-CoA synthetase long-chain family member 1, codes for a protein that assists in the biosynthesis of lipids and degradation of fatty acids, and SNPs within this gene have been associated with chronic diseases like diabetes. 54 Finally, ELF1 (Gene ID: 1997), also known as E74 like E26 transformation-specific related transcription factor 1, is an important positive regulator of the Hox cofactor Myeloid ectropic viral integration site 1 (MEIS1) which is involved in developmental processes. 55 Of all these DMPs and their annotated genes, RUNX1 is the only gene in which differential methylation has previously been associated with OA in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ACSL1 (Gene ID: 2180), also known as acyl-CoA synthetase long-chain family member 1, codes for a protein that assists in the biosynthesis of lipids and degradation of fatty acids, and SNPs within this gene have been associated with chronic diseases like diabetes. 47 Lastly, ELF1 (Gene ID: 1997), also known as E74 like E26 transformationspecific related transcription factor 1, is an important positive regulator of the Hox cofactor Myeloid ectropic viral integration site 1 (MEIS1) which is involved in developmental processes. 48 Out of all of these DMPs and their annotated genes, RUNX1 is the only gene in which differential methylation has previously been associated with OA in humans.…”
Section: Discussionmentioning
confidence: 99%